The Development and Evaluation of the Intersectional Privilege Screening Inventory for Use With Counselors‐in‐Training. (8th June 2020) - Pester, Danielle A.; Lenz, A. Stephen; Watson, Joshua C.
Abstract : As counselor preparation programs are compelled to demonstrate student social and cultural competence, valid inventories are needed to measure development consistent with contemporary standards. The Intersectional Privilege Screening Inventory was created for this purpose, was assessed using 4 types of validity evidence, and has results supporting its use in student development.